2013
DOI: 10.1084/jem.20122762
|View full text |Cite
|
Sign up to set email alerts
|

Lung dendritic cells induce migration of protective T cells to the gastrointestinal tract

Abstract: Lung DCs induce the expression of gut-homing molecules on T cells, resulting in their migration to the GI tract and protection against Salmonella infection after immunization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 72 publications
4
86
1
2
Order By: Relevance
“…Thus specific DC populations and local factors result in preferential generation of IgA-producing B cells in the GALT and MLNs and imprinting of lymphocytes with the specific gut homing receptors α4β7 integrin, CCR9 and CCR10 [66,71]. In support of the idea of a common mucosal immune system, lung DCs have also been shown to be capable of imprinting a GIT homing phenotype on T cells allowing for their migration to the gut where they facilitated protection against an intestinal Salmonella infection [79]. Once primed, lymphocytes exit the PPs and the MLNs via the thoracic duct and blood and finally migrate back to the gut via homing receptors and cognate ligands expressed only in the gut tissue.…”
Section: Gut Immune Responsesmentioning
confidence: 92%
“…Thus specific DC populations and local factors result in preferential generation of IgA-producing B cells in the GALT and MLNs and imprinting of lymphocytes with the specific gut homing receptors α4β7 integrin, CCR9 and CCR10 [66,71]. In support of the idea of a common mucosal immune system, lung DCs have also been shown to be capable of imprinting a GIT homing phenotype on T cells allowing for their migration to the gut where they facilitated protection against an intestinal Salmonella infection [79]. Once primed, lymphocytes exit the PPs and the MLNs via the thoracic duct and blood and finally migrate back to the gut via homing receptors and cognate ligands expressed only in the gut tissue.…”
Section: Gut Immune Responsesmentioning
confidence: 92%
“…53,54 Although there have been reports of mucosal compartmentalization restricting induction of intestinal immune responses by intranasal immunization, a recent study by Ruane et al showed that intranasal immunization stimulated a 4 b 7 expression on T cells in the lung and the mediastinal lymph nodes and induced cell migration to the GI tissues. 94 This activity was mediated by lung DCs, in a process similar to that exhibited by mesenteric lymph node DCs. Consistent with this concept, DNA encoding HIV-1 gag fused to lysosome-associated membrane protein (LAMP/gag) delivered intranasally to neonatal mice was shown to elicit IgA, IgG, and IFN-c + T cell responses in the intestines.…”
Section: Intranasal Vaccinationmentioning
confidence: 94%
“…In fact, not only pathogenic microorganisms but also commensal and symbiont microorganisms (organisms making up the microbiome) are especially present in those tissues prone to NP exposure, like the mucosae and the skin. Since the reciprocal interactions between the microbiome and the immune system (22)(23)(24) influence a delicate balance of defensive/proinflammatory and tolerance/anti-inflammatory responses (25)(26)(27)(28)(29)(30), the presence of NPs may represent a factor perturbing host-microbe interactions and, in the end, tissue homeostasis. Such a possibility is indeed suggested by the little evidence that is available: endocytosed NPs and the lipopolysaccharide (LPS) of Gram-negative bacteria synergistically increase the levels of cytokine production by monocytes, macrophages, and DCs (17,(31)(32)(33)(34)(35)(36) and cytotoxicity in A549 epithelial cells (37).…”
mentioning
confidence: 99%